THE ROLE OF ANCESTOR WORSHIP IN CHINESE RELIGION AND CULTURE: AN EXAMINATION OF ITS SIGNIFICANCE IN CONFUCIANISM AND TAOISM - Liu, Dongwang (European journal for philosophy of religion, 2023)
Ancestor worship is a diffusive religion. Different nationalities may have different ideas about ancestors, but ancestor worship plays the same role. In the development of modern society, Ancestor worship still plays an important role in the demand for human psychology, the shaping of individuals, the stable development of families, and the cohesion of ethnic groups. The development and inheritance basis of ancestor worship is closely related to Chinese religion and culture, and the integration of the two has also promoted the continuous inheritance and development of Chinese religion and culture. At the same time, ancestor worship is also the concrete manifestation of filial piety advocated by Confucianism and Taoism in Chinese traditional culture. By analyzing the basis of the formation of ancestor worship and its inheritance characteristics, this paper discusses the important role of ancestor worship in Chinses religion and culture and further discusses the influence of Confucianism and Taoism on the inheritance of ancestor worship by combining the relationship between filial piety and ancestor worship in Confucianism and Taoism.